2003
DOI: 10.1097/01.ju.0000094188.69698.f8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Synchronous Twin Pulse Technique for Shock Wave Lithotripsy: Determination of Optimal Parameters for In Vitro Stone Fragmentation

Abstract: The efficacy of synchronous twin pulse technology improves as the number of shock waves and power increase. A 90-degree angle between the shock wave reflectors is advantageous for certain stones (that is cystine and plaster of Paris) but it is not a factor for other stone compositions. THSWL has satisfactory disintegrative efficacy for human stones, especially COM and cysteine calculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This technique intensifies and localizes the cavitation effects by the interacting focal zones of both reflectors, resulting in a better quality and rate of stone disintegration, especially with a right angle between the axes of the reflectors [8,9]. This device had good in vitro disintegrative efficacy for both artificial (Bon(n)‐stones, and plaster of Paris) and human stones (COM, brushite and cystine) with better efficacy as the number of shock waves and the power were increased [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique intensifies and localizes the cavitation effects by the interacting focal zones of both reflectors, resulting in a better quality and rate of stone disintegration, especially with a right angle between the axes of the reflectors [8,9]. This device had good in vitro disintegrative efficacy for both artificial (Bon(n)‐stones, and plaster of Paris) and human stones (COM, brushite and cystine) with better efficacy as the number of shock waves and the power were increased [10].…”
Section: Discussionmentioning
confidence: 99%
“…On 1999 we developed the bidirectional synchronous twin‐pulse technique with variable angles between the shock wave reflectors, and found that it improved the quality and rate of stone disintegration in vitro (especially with a right angle between the reflectors) [8]. The disintegrative efficacy for both artificial and human stones was improved as the number of shock waves and the power were increased [9,10]. Bidirectional synchronous 90° twin‐pulse‐induced tissue damage (acutely) appeared to be minimal when compared with a single pulse [11].…”
Section: Introductionmentioning
confidence: 99%
“…[1415] The rationale in this concept is, that “filling” the negative part of the pressure wave with a positive pressure pulse would theoretically result in improved fragmentation and reduced cavitation with reduced parenchymal damage.…”
Section: Shockwave Sourcesmentioning
confidence: 99%
“…The idea was that the two waves would impact on the target yet cancel out peripheral damaging effects. It was found that this technique reduces and localizes the cavitation effects, together with improving the quality and rate of stone disintegration, especially with a right‐angle between the axes of the SW reflectors [6,7]. There was minimal tissue damage compared with the standard single‐pulse method in an animal study [8].…”
Section: Introductionmentioning
confidence: 99%